2011
DOI: 10.1071/hc11307
|View full text |Cite
|
Sign up to set email alerts
|

Patient Dashboard: the use of a colour-coded computerised clinical reminder in Whanganui regional general practices

Abstract: INTRODUCTION: Clinical reminders have been shown to help general practice achieve an increase in some preventive care items, especially if they identify a patient’s eligibility for the target item, prompt clinicians at the right time, provide a fast link to management tools and facilitate clinical recording. WRPHO has introduced the Patient Dashboard clinical reminder and monitored its impact on health targets. Aim: This paper reports the impact of a computerised colour-coded clinical reminder on achieving agr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 2 publications
0
16
0
Order By: Relevance
“…One study published three papers from data obtained at different periods [32–34], and the most recent paper was included [33]. A total of 9 studies fulfilled the inclusion criteria and were included [27, 33, 35, 36, 47, 54, 55, 58, 59]. Forward and backward searches of the reference lists and bibliography citations of the 9 studies yielded an additional 16 studies [37, 39, 48–53, 56, 57, 60–65] and resulted in a total of 25 studies for qualitative synthesis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study published three papers from data obtained at different periods [32–34], and the most recent paper was included [33]. A total of 9 studies fulfilled the inclusion criteria and were included [27, 33, 35, 36, 47, 54, 55, 58, 59]. Forward and backward searches of the reference lists and bibliography citations of the 9 studies yielded an additional 16 studies [37, 39, 48–53, 56, 57, 60–65] and resulted in a total of 25 studies for qualitative synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Two authors provided the requested information [27, 37] while authors of the other four studies were either not contactable or stated that they no longer had access to the data. These four studies [35, 36, 39, 65] were excluded, and the final number of studies included in the meta-analysis was 21. Figure 1 illustrates the process of study search and selection.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Source Primary care practitioner [40]- [42], [45], [47]- [49], [52] General Practitioner [34] Clinician [9], [17]- [21], [31], [46], [50], [55], [56], [58], [59] Physician [5], [35], [39], [42], [44], [53] Nurse [4], [33], [36], [38], [42], [50] Medical Staff [4], [6], [7], [19], [21], [33], [37], [39], [43], [50], [51], [57] Pharmacist [40], [60] Administrator and Managers [36], [53], [57] Patient [4], [17]- [21], [52],…”
Section: Usersmentioning
confidence: 99%
“…Furthermore, for a useful design, not only colours needs to be selected based on the medical experts' suggestions regarding colour semantics of the domain, but also needs be chosen based on other users' characteristics (such as colour-blind users) [4]. In our analysis in some cases the traffic light colour coding principle was adopted in dashboards' design [7], [18], [38], [39], [41], [42], [44], [47], [50]- [52]. As an example, Starmer et al (2008), [7] used a simple color scheme of (red, yellow and green) to indicate several conditions compliance with processes.…”
Section: Dashboardsmentioning
confidence: 99%
“…Existing research has identified different types of DSDM tools, from patient health self-tracking apps that share data with clinicians for personalized care planning [16]; to system dashboards used by clinicians to interlink data from different sources and support decision-making around patient treatment [18]. This paper focuses on data dashboards due to their extensive use in healthcare delivery, including hospital admissions reduction [16], best practice adherence [17], high risk patients' identification [27] and medication monitoring [18]. Related work highlights the challenge of integrating systems into clinical use, due to poor cultural fit or lack of integration and linkage to other key clinical systems [5,6].…”
Section: Introductionmentioning
confidence: 99%